The Effect of Job Stress, Work Environment and Compensation on Job Satisfaction with Motivation as an intervening variable at PT. Setia Kawan Grup: Pengaruh Stres Kerja, Lingkungan Kerja dan Kompensasi terhadap Kepuasan Kerja dengan Motivasi sebagai variabel intervening pada PT. Setia Kawan Grup - Mahdiana, Dwi; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine the effect of work stress, work environment, and compensation on job satisfaction with motivation as an intervening variable. The approach used in this research is a quantitative approach. The sample in this study were 70 employees at PT. Loyal Friends Group. The data used in this study is questionnaire data. Data collection techniques using questionnaires, interviews, observations, and documentation. Data analysis using software smartPLS 3.2.8. The results obtained from the path analysis showed that job stress had no significant effect on job satisfaction, job stress had a significant effect on motivation, work environment had no significant effect on job satisfaction, work environment had no significant effect on motivation, compensation had a significant effect on job satisfaction, compensation has a significant effect on motivation, motivation has a significant effect on job satisfaction, job stress does not have a significant effect on job satisfaction through the motivation variable as an intervening variable, the work environment does not have a significant effect on job satisfaction through the motivation variable as an intervening variable, compensation has a significant effect on job satisfaction through motivation variable as an intervening variable. Keywords: Job Stress, Work Environment, Compensation, Job Satisfaction, Motivation.